2006
DOI: 10.1007/s00125-006-0322-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal telomere attrition as a mechanism for the increased risk of epithelial cancers and senescent phenotypes in type 2 diabetes

Abstract: Telomeres are the repeat DNA sequences at the end of chromosomes necessary for successful DNA replication and chromosomal integrity. Telomeres shorten at cell division at a rate determined by oxidative DNA damage, and cells are triggered into replicative senescence once telomeres shorten to a critical length. Telomere-related chromosomal maintenance also has a role in carcinogenesis. Type 2 diabetes is characterised by increased oxidative stress, increased oxidative DNA damage, senescent retinal and renal phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…Moreover, type 2 diabetes produces a synergistic effect on liver fibrosis progression in patients with HCV infection (24) and, therefore, increases the risk of hepatocellular carcinoma. Second, liver damage may be exacerbated by oxidative stress and telomere shortening caused by long-term diabetes (26). Telomere shortening limits the proliferative capacity and induces DNA damage, replicative senescence, apoptosis, and chromosomal instability in hepatocytes (1,26).…”
Section: Type 2 Diabetes Impact On Hepatocellular Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, type 2 diabetes produces a synergistic effect on liver fibrosis progression in patients with HCV infection (24) and, therefore, increases the risk of hepatocellular carcinoma. Second, liver damage may be exacerbated by oxidative stress and telomere shortening caused by long-term diabetes (26). Telomere shortening limits the proliferative capacity and induces DNA damage, replicative senescence, apoptosis, and chromosomal instability in hepatocytes (1,26).…”
Section: Type 2 Diabetes Impact On Hepatocellular Carcinomamentioning
confidence: 99%
“…Second, liver damage may be exacerbated by oxidative stress and telomere shortening caused by long-term diabetes (26). Telomere shortening limits the proliferative capacity and induces DNA damage, replicative senescence, apoptosis, and chromosomal instability in hepatocytes (1,26). Third, increased insulin levels also stimulate cell growth and DNA synthesis, both of which are involved in carcinogenesis and neoplastic differentiation, by decreasing apoptosis and increasing mitogenesis (27,28).…”
Section: Type 2 Diabetes Impact On Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental studies have indicated that individuals with relatively short mean telomere lengths might have an increased risk of mortality from multiple diseases (20,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In particular, five studies have examined the associations between breast cancer risk and mean telomere length (35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Feto-placental telomere attrition is an attractive hypothetical bridge between the adverse intrauterine environment and preprogramming of the offspring towards senescent phenotypes [19][20][21], as an adverse intrauterine environment increases oxidative damage to feto-placental DNA and fetal vascular endothelium [22][23][24]. We have previously suggested that this mechanism could account for a senescent phenotype in the adult offspring of women with type 1 diabetes [25].…”
Section: Introductionmentioning
confidence: 99%